(untitled) (Public Sector Economics - submission site, 2021)
This paper explores the use of accounting information at the local and regional government level in Croatia. Accountants provide cost accounting information mainly on request from internal users. The usefulness of this information is observed from the accountant viewpoint, in order to perceive accountants’ understandings of how decision-makers use accounting data. A questionnaire was used as a research instrument in order to assess the level of accounting information use and usefulness among governing politicians and other public managers. Empirical results indicate that the legal representatives of the budgetary users (public managers) are more inclined than governing politicians to use accounting information in decision-making. Cost accounting information is most useful for planning and control and least beneficial when prices of public services are being set. Public sector cost accounting in Croatia is well implemented and constraints on its further development are not highly in evidence.